Exercise therapy in patients with hip osteoarthritis: Effect on hip muscle strength and safety aspects of exercise—results of a randomized controlled trial. Issue 3 (4th May 2017) - Steinhilber, Benjamin; Haupt, Georg; Miller, Regina; Janssen, Pia; Krauss, Inga
Abstract: Purpose : To evaluate the effect of an exercise therapy concept (the Tübingen exercise therapy approach THüKo) for increasing hip muscle strength (HMS) in patients with hip osteoarthritis (OA), and to investigate whether patients do adhere to the intervention and if there are any adverse events related to the intervention. Methods : A total of 210 hip OA patients (89 females, 121 males) were randomized into a 12-week exercise intervention (THüKo) including group sessions (1/week) and home exercising (2/week), a placebo ultrasound group (1/week) or a control group (no treatment). HMS was measured as isometric peak torque of hip abduction, adduction, flexion, and extension. Adherence to exercise and safety aspects were monitored as additional outcomes. Results : Baseline adjusted post intervention HMS of the THüKo group were higher compared to the control group (differences of 0.11–0.27 Nm/kg, p  < 0.01) and to the placebo ultrasound group (differences of 0.09–0.19 Nm/kg, p  < 0.01). Adherence to exercise was high (about 90%). No subject had to refuse from training because of an exercise related adverse event and exercise related pain was only of intermittent nature without sustainable adverse effects. Conclusions : The Tübingen exercise therapy approach has shown to have a significant positive effect on HMS. Its implementation has shown to be feasible and safe according to the percentage of exercise participation and the absence of sustainable adverse events.